GaAs nanoscale membranes: prospects for seamless integration of III–Vs on silicon. Issue 2 (12th December 2019) - Raya, Andrés M.; Friedl, Martin; Martí-Sánchez, Sara; Dubrovskii, Vladimir G.; Francaviglia, Luca; Alén, Benito; Morgan, Nicholas; Tütüncüoglu, Gözde; Ramasse, Quentin M.; Fuster, David; Llorens, Jose M.; Arbiol, Jordi; et al.
Abstract : Selective area epitaxy of GaAs nanoscale membranes on silicon. Small apertures result in a majority defect-free structures. Abstract : The growth of compound semiconductors on silicon has been widely sought after for decades, but reliable methods for defect-free combination of these materials have remained elusive. Recently, interconnected GaAs nanoscale membranes have been used as templates for the scalable integration of nanowire networks on III–V substrates. Here, we demonstrate how GaAs nanoscale membranes can be seamlessly integrated on silicon by controlling the density of nuclei in the initial stages of growth. We also correlate the absence or presence of defects with the existence of a single or multiple nucleation regime for the single membranes. Certain defects exhibit well-differentiated spectroscopic features that we identify with cathodoluminescence and micro-photoluminescence techniques. Overall, this work presents a new approach for the seamless integration of compound semiconductors on silicon.